MENUMBUHKAN LOYALITAS PENGUNJUNG TEMPAT WISATA MELALUI DIMENSI EXPERIENTAL MARKETING - Wiwik Widiyanti (RJABM (Research Journal of Accounting and Business Management), 2022)
The Loyalty of visitors is very important for the survival of the Insani Herbal Garden. This can be grown through a pleasant experience that is summarized in the experiential marketing dimension. The purpose of this study was to determine how the influence of experiential marketing dimensions on loyalty, either simultaneously or partially. The Descriptive quantitative methods were chosen as a research approach with data collection techniques using questionnaires. Samples were taken as many from as 100 respondents. The data were processed using the SPSS 16 application. The results of the research on partial hypothesis testing for the dimensions of sense, feel, think and act significantly affected loyalty, while the related dimension did not significantly affect visitor loyalty. In contrast to simultaneous hypothesis testing, the five dimensions of experiential marketing significantly affect visitor loyalty. The results of this study are expected to be taken into consideration by the management of Taman Herbal Insani in advancing their business